Utilisation of Online Public Access Catalogue (OPAC) among Students of Federal University of Agriculture, Abeokuta, Nigeria - Abayomi, Owolabi Kehinde; Susan, Adeyeye Yemisi; S.S, Musa.; Dolapo, Pelemo Grace; Oluronke, Adesina A (Gyan Management Journal, 2022)
Libraries house information in various forms such as  prints and non-print materials. Considering the avail ability of various resources in the library, there is need  for information retrieval systems that will enable users  to have access to required information as at when  needed. Modern libraries are increasingly being rede fined to provide unrestricted access to information in  various sources and formats. Academic libraries differ  from one another in many respects, but they all have the  same basic function, which is to aid the parent institu tion to carry out its objectives in the areas of teaching,  learning, and community development. Libraries con tribute to the realisation of these objectives and support
Keywords: (OPAC); Agriculture; Abeokuta; Nigeria